Effectiveness of Pregnancy Check Boxes on Death Certificates in Identifying Pregnancy-Associated Mortality - Horon, Isabelle L. (Association of Schools of Public Health, 2011)
OBJECTIVES: Information that would allow the identification of women who were pregnant at the time of death or within the year preceding death has historically been underreported on death certificates. As a result, the magnitude of the problem of pregnancy-associated mortality is underestimated. To improve the identification of these deaths, check boxes for reporting pregnancy status have been added to death certificates in a number of states. We used multiple external data sources to determine whether check boxes have been effective in identifying pregnancy-associated deaths. METHODS: We collected data on deaths occurring among pregnant or recently pregnant women residing in Maryland during the years 2001–2008 using multiple data sources. We determined the percentage of these deaths that could be identified through check boxes placed on death certificates. RESULTS: Overall, 64.5% of pregnancy-associated deaths were identified through pregnancy check boxes on death certificates, including 98.1% of maternal deaths—defined as deaths occurring during pregnancy or within 42 days of delivery from any cause related to or aggravated by the pregnancy or its management but not from accidental or incidental causes—and 46.7% of deaths from nonmaternal causes, such as homicide, suicide, accidents, and substance abuse. CONCLUSIONS: Check boxes on death certificates are effective in identifying pregnancy-associated deaths resulting from maternal causes. However, they are far less effective in identifying deaths resulting from nonmaternal causes, such as homicide, accidental death, and substance abuse, which represent three of the four leading causes of pregnancy-associated death in Maryland.